Sonate, Pathètique pour le piano forte dediée à Son altesse Monsieur le Prince de Lichnowsky, par L. van Beethoven. (Nouv. éd. exacte) ... - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Czerny, Carl, 1791-1857 (editor):::Contributor:::::::::::: (R. Cocks & Co.; London; United Kingdom, 2022)
Early edition of the Sonata no. 8 in C Minor, op. 13, edited by Carl Czerny and published by R. Cocks in London as no. 3 of the series "Soirées des pianistes"; variant of the edition published in the "Beethoven's Masterpieces" series.